Análise da percepção do trabalhador sobre os riscos no ambiente de trabalho: estudo de caso em unidade de operação de empresa de energia brasileira - Silva, Bernardete Ferreira da (2011)
Understanding if the employee perceives the risks of working environment becomes increasingly important to the company that seeks to improve its Health and Safety Management Labor and enhance their public image in today's competitive market, where companies committed to environmental responsibility tend to achieve greater competitive advantage to society and investors. Investigate and analyze the risk perception of workers as a component of the causes of occupational accidents enables the adoption of administrative measures specific to this cause with effect in reducing the occurrence of accidents. Thus, this research aims at analyzing the perception of workers about the risks of their work environment. For the development of research, was selected one of the Operating Units in the business of supply of petroleum and its derivatives in the market belonging to a Brazilian energy company identified as the highest incidence of occupational injuries during the period 2008-2010. In a detailed analysis of these accidents, identifies himself as a critic of Industrial Painting Service due to the higher number of workplace accidents recorded in the period mentioned above and whose reports for Accident Research and Analysis failure or lack of risk perception of the worker is considered one of the causes of these accidents. As the main tool for field research, is used a structured questionnaire, divided into two parts: Part I - Employee Data and Part II - Perception of Risk. Part II of the questionnaire is based on the Standard Execution Aspects and Hazard Identification and Risk Assessment and data from the database of Aspects, Impacts, Dangers and Consequences of Unit Operation object of research, referring to the Industrial Painting Service. Through a quantitative approach, the survey results indicate that only a minority of workers perceive the risks of their work environment and the Risk Communication Program Management System Occupational Health and Safety Unit is insufficient to prepare worker to understand these risks and develop safe attitudes